The Effect of Electronic Word-Of-Mouth (Ewom) On Brand Image and Purchase Intention: A Conceptual Paper - Al Halbusi, H.; Tehseen, S.
The purpose of this research paper is to investigate the effect of Electronic Word-of-Mouth (eWOM) on brand image and purchase intention. A study on Malaysia’s automobile industry focusing on Malaysian branded cars. However, before we embark to the details of this research, the paper will give a synopsis of the study. Initially this will highlight commence with a research background followed by a problem statement then significance of the study which will eventually be trailed with the research questions, research objectives and lastly, limitations will be elucidated.